Optimization Of Culture Conditions For The Production Of Xylanase By Two Thermophilic Fungi Under Solid State Fermentation (Journal of the Asiatic Society of Bangladesh, Science, 2013)
Two thermophilic fungi, Thermomyces lanuginosus BPJ-10 and Rhizomucor pusillus BPJ-2 were studied under solid state fermentation (SSF) using wheat bran for the production of thermostable xylanase. The optimum time required for the production of xylanase was found to be 4 days and 7 days for R. pusillus BPJ-2 and T. lanuginosus BPJ-10 respectively. The optimum temperatures for the production of xylanase by R. pusillus BPJ-2 and T. lanuginosus BPJ-10 were 45°C and 50°C respectively. The maximum activity of xylanase (1.685 IU/ml and 0.075 IU/ml) was exhibited by T. lanuginosus BPJ-10 and R. pusillus BPJ-2 at pH 7.0 and pH 4.0 respectively. The optimum moisture content for maximum xylanase production was 90% for both fungi. J. Asiat. Soc. Bangladesh, Sci. 39(1): 43-51, June 2013 DOI: http://dx.doi.org/10.3329/jasbs.v39i1.16032